2018
DOI: 10.3348/kjr.2018.19.3.410
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-Coated Balloon Angioplasty for Early Restenosis of Central Veins in Hemodialysis Patients: A Single Center Initial Experience

Abstract: ObjectiveTo report the results of angioplasty with paclitaxel-coated balloons for the treatment of early restenosis of central veins in hemodialysis patients.Materials and MethodsSixteen patients (9 men and 7 women; mean age 65.8 ± 14.4 years; range, 40–82 years) with 16 episodes of early restenoses of central veins within 3 months (median patency duration 2.5 months) were enrolled from January 2014 to June 2015. Ten native central veins and 6 intra-stent central veins were treated with double paclitaxel-coate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
2
19
0
3
Order By: Relevance
“…Massmann et al [20] showed that PCBA provided significantly better freedom from target tissue revascularization than conventional BA. Other two publications also showed similar results [21,22]. The mechanism of paclitaxel is the promotion of cell cycle arrest in the G1 phase without apoptosis of the cells that causes the reduction of the neo-intimal hyperplasia of the venous wall [22].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Massmann et al [20] showed that PCBA provided significantly better freedom from target tissue revascularization than conventional BA. Other two publications also showed similar results [21,22]. The mechanism of paclitaxel is the promotion of cell cycle arrest in the G1 phase without apoptosis of the cells that causes the reduction of the neo-intimal hyperplasia of the venous wall [22].…”
Section: Discussionmentioning
confidence: 67%
“…Other two publications also showed similar results [21,22]. The mechanism of paclitaxel is the promotion of cell cycle arrest in the G1 phase without apoptosis of the cells that causes the reduction of the neo-intimal hyperplasia of the venous wall [22]. However, there are still no data showing the efficacy of primary PCBA in chronic CVO.…”
Section: Discussionmentioning
confidence: 76%
“…В-четвертых, мы не учитывали тип баллона, его рабочее давление и протяженность стеноза. Есть основания полагать, что эти факторы также имеют клиническое значение [66,[70][71][72]. В-пятых, мы не включали в исследование пациентов, у которых АВФ была сформирована при помощи синтетического сосудистого протеза, а также тех пациентов, где протез был использован при реконструкциях (такие пациенты были исключены из исследования).…”
Section: ограничения исследованияunclassified
“…По мере накопления опыта и завершения клинических исследований были предложены подходы к улучшению результатов эндоваскулярных вмешательств. Так, предложено использовать стенты [24] и стент-графты [25], применять баллонные катетеры с лекарственным покрытием [26] и катетеры с баллонами высокого давления [27]. Такое многообразие доступных методов воздействия на пораженный сегмент вен компенсируется отсутствием конкретных показаний, позволяющих выбрать оптимальный метод, что в значительной мере компрометирует эндоваскулярные вмешательства.…”
Section: Introductionunclassified
“…Есть исследования, которые свидетельствуют в пользу того, что использование режущих баллонов может быть ассоциировано с большей вторичной проходимостью по сравнению с использованием стандартных баллонных катетеров [48] и катетеров высокого давления [49]. Кроме того, использование баллонных катетеров с лекарственным покрытием может обеспечить некоторое преимущество по сравнению со стандартными баллонами [50,51]. Однако на данный момент недостаточно данных, чтобы однозначно сделать выбор в пользу тех или иных баллонных катетеров.…”
Section: методы лечения стенотических поражений центральных венunclassified